Maternal immunization and vitamin A sufficiency impact sow primary adaptive immunity and passive protection to nursing piglets against porcine epidemic diarrhea virus infection - Amimo, Joshua O.; Michael, Husheem; Chepngeno, Juliet; Jung, Kwonil; Raev, Sergei A.; Paim, Francine C.; Lee, Marcia V.; Damtie, Debasu; Vlasova, Anastasia N.; Saif, Linda J. (Frontiers in Immunology, 2024)
Porcine epidemic diarrhea virus (PEDV) causes a highly contagious enteric disease with major economic losses to swine production worldwide. Due to immaturity of the neonatal piglet immune system, and given the high virulence of PEDV, improving passive lactogenic immunity is the best approach to protect suckling piglets against the lethal infection. We tested whether oral vitamin A (VA) supplementation and PEDV exposure of gestating and lactating VA deficient (VAD) sows would enhance their primary immune responses and boost passive lactogenic protection against PEDV challenge of their piglets. We demonstrated that PEDV inoculation of pregnant VAD sows in the 3 rd trimester provided higher levels of lactogenic protection of piglets as demonstrated by >87% survival rates of their litters compared with <10% in mock litters, and that VA supplementation to VAD sows further improved piglets' survival rates to >98%.We observed significantly elevated PEDV IgA and IgG antibody (Ab) titers and Ab secreting cells (ASCs) in VA sufficient (VAS)+PEDV and VAD+VA+PEDV sows, with the latter maintaining higher Ab titers in blood prior to parturition, and in blood and milk throughout lactation. The litters of VAD+VA+PEDV sows also had the highest serum PEDV neutralizing Ab titers at piglet post-challenge days (PCD) 0 and 7, coinciding with higher PEDV IgA ASCs and Ab titers in blood and milk of their sows, suggesting an immunomodulatory role of VA in sows. Thus, sows that delivered sufficient lactogenic immunity to their piglets, provided the highest passive protection against PEDV challenge. Maternal immunization during pregnancy (±VA) and VA sufficiency enhanced sow primary immune responses, expression of gut-mammary gland trafficking molecules and passive protection of their offspring. Our findings are relevant to understanding the role of VA in the Ab responses to oral attenuated vaccines that are critical for successful maternal vaccination programs against enteric infections in infants and young animals.